2023
DOI: 10.15541/jim20220532
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior and Mechanism of Aluminum-rich CMAS on Rare-earth Silicate Environmental Barrier Coatings:

Abstract: Environmental barrier coatings (EBCs) are expected to be applied to the hot-section components of a new generation of high thrust-to-weight ratio aero-engines. Rare-earth silicates have been acknowledged as promising alternatives to EBC materials due to their superior high-temperature phase stability, suitable coefficient of thermal expansion and long durability in water vapor. However, the calcium-magnesium-alumino-silicates (CMAS) molten salt corrosion under service conditions have become a bottleneck that l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…1,2 Rare-earth (RE) silicates are considered as promising novel E/TBC candidates, which exhibit excellent mechanical properties and thermal properties, such as low modulus, good damage tolerance, low thermal conductivity, coefficient of thermal expansion (CTE), and so on. [3][4][5][6][7] Among all silicates, lutetium silicates are widely studied owing to their excellent CMAS corrosion resistance and similar CTE values with SiC and mullite. 8 Tian et al observed that Lu 2 SiO 5 has excellent hightemperature durability and low thermal conductivity (1.72 W ⋅ m −1 ⋅ K −1 at 1273 K).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…1,2 Rare-earth (RE) silicates are considered as promising novel E/TBC candidates, which exhibit excellent mechanical properties and thermal properties, such as low modulus, good damage tolerance, low thermal conductivity, coefficient of thermal expansion (CTE), and so on. [3][4][5][6][7] Among all silicates, lutetium silicates are widely studied owing to their excellent CMAS corrosion resistance and similar CTE values with SiC and mullite. 8 Tian et al observed that Lu 2 SiO 5 has excellent hightemperature durability and low thermal conductivity (1.72 W ⋅ m −1 ⋅ K −1 at 1273 K).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies mainly focused on the intrinsic properties of precorrosion coatings and their micromorphology in postservice stage. 5,11,13 Actually, a lot of experimental works reported that the products came to being from the reaction between RE silicates and CMAS with the progress of corrosion. A fine apatite phase layer was observed on the surface of 𝛾-Y 2 Si 2 O 7 under CMAS corrosion, and anorthite, pseudowollastonite, apatite, and so on, also were detected between the RE 2 Si 2 O 7 (RE = Yb, Lu, La, Gd, Eu, Sc, and Y) and CMAS.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…28 Many of the modeled CMAS compositions in previous studies were based on engine sediments, which are quite different from the natural mineral sources of CMAS. [29][30][31][32] Stokes et al investigated the effect of different CMAS (Ca/Si ratio = 0.635, 0.478, and 0.096) on the corrosion behaviors for RE 2 Si 2 O 7 (RE = Er, Dy, Gd, and Nd) bulk materials, and showed that an increase in the CaO content resulted in the generation of apatite phases during the corrosion process. 33 Summers et al investigated the corrosion behaviors of Y 2 Si 2 O 7 blocks against CMAS with different compositions at 1300 • C and 1400 • C, respectively.…”
Section: Introductionmentioning
confidence: 99%